Vibration of the plant substrate generated by workers' stridulation during fungus garden cultivation in Atta laevigata (Smith) (Hymenoptera: Formicidae) - Carlos, Amanda Aparecida; Diniz, Eduardo Arrivabene; da Silva, Sandra Verza; Bueno, Odair Correa (EntomoBrasilis, 2018)
Abstract. The communication between leaf-cutting ants occurs through chemical interactions and sound, which are important processes in the complex social system of these organisms. Studies have focused on the characterization and importance of stridulation and vibration of the substrate for ants in general. However, for leaf-cutting ant species, little information is available about the characterization and the function of vibration of the substrate during preparation and incorporation of plant material into the symbiotic fungus by workers. Therefore, the objective of the present study was to describe the vibration in Eucalyptus leaves generated by the stridulation of Atta laevigata (Smith) workers during processing and incorporation of the plant material into the symbiotic fungus, and to discuss its possible function. Vibrational signals were recorded with a laser vibrometer. The amplitudes of the emitted signals varied according to the behaviors performed, that is, each behavior showed a characteristic amplitude. Thus, the vibration in the leaves probably can aid in the efficiency of these ants during the processing of the vegetal material for the incorporation in its symbiont. Vibração do substrato vegetal gerada pela estridulação de operárias durante o cultivo do fungo em Atta laevigata (Smith) (Hymenoptera: Formicidae) Resumo. A comunicação entre as formigas cortadeiras ocorre por meio da interação química e do som, processos importantes no complexo sistema social destes organismos. Existem vários estudos enfocando a caraterização e a importância da estridulação e vibração do substrato para as formigas em geral. Contudo, pouco se tem descrito para as espécies de formigas cortadeiras sobre a caracterização e função da vibração do substrato durante o preparo e a incorporação do material vegetal pelas operárias no fungo simbionte. Assim, o presente trabalho descreveu a vibração nas folhas de Eucalyptus sp. gerada pela estridulação das operárias de Atta laevigata (Smith) durante o processamento e incorporação destas folhas no fungo simbionte, além de interpretar sua possível função. Os sinais vibratórios foram gravados com um vibrômetro a laser. As amplitudes dos sinais emitidos variaram conforme os comportamentos executados, ou seja, cada comportamento apresentou uma amplitude característica. Desse modo, a vibração nas folhas provavelmente pode auxiliar na eficiência dessas formigas durante o processamento do material vegetal para a incorporação no seu simbionte.